La Celestina en el Índice: Argumentos de una censura - Donatella Gagliardi (Celestinesca, 2021)
Should La Celestina be deemed a perverse and perverting work, or rather a book of exemplary morals? Can its cathartic ending compensate for the blasphemy and lewd pleasure which mark it? Is malice merely in the eyes of the depraved reader or does it lie concealed between the lines of the text? These and other questions were raised with increasing concern by religious and scholars as the publishing success of the Tragicomedy was confirmed. This article traces three centuries of literary censorship, reconstructing and analysing the arguments of the moralists which ended up causing, in the late 18th century, the final sentence against La Celestina.